AB1132 THE ROLE OF PET/CT IN THE MANAGEMENT OF GIANT CELL ARTERITIS. (June 2019) - Croce, Alessandro; Bellan, Mattia; Pedrazzoli, Roberta; Sola, Daniele; Puta, Erinda; Sacchetti, Gian Mauro; Soddu, Daniele; Zecca, Erika; Pirisi, Mario; Sainaghi, Pier Paolo
Abstract : Background: Giant cell arteritis (GCA) is a large vessel vasculitis that affects the aorta and/or its major branches including the superficial temporal artery. Together to cranial symptoms such as headache and visual disturbances, extra cranial manifestations have been widely reported, sometimes as unique clinical presentation. Several imaging modalities are available to evaluate aortic involvement including fluorodeoxyglucose (FDG) positron emission tomography (PET), however there are few reports that analyzed the impact of the findings of this advanced imaging in predicting outcomes of the disease. Objectives: To assess the utility of PET in disease extension assessment to predict, together to clinical manifestations, the disease evolution. Methods: We retrospectively reviewed all the clinical records of patients receiving a diagnosis of large vessel vasculitis from 1 st January 2010 to 1 st January 2016 at a tertiary immunorheumatology clinic of a university Hospital, who underwent a PET. Clinical, laboratory, and imaging data were collected. Non-parametric analysis was performed. Results: We recruited 19 patients (10 females, 52.6%). The median age was 74.0 [65.5-76.0]; at the diagnosis, the median erythrocyte sedimentation rate (ESR) was 65.5 [49.0-86.0], while C-reactive protein (CRP) was 8.5 [5.5-14.0]. 12 patients showed a typical cranial GCA (63.2%), while 7 (36.8%) were diagnosed with extracranial GCA. The two groups were comparable at diagnosis for age, gender, median ESR and CRP. Interestingly, the PET was significative for aortitis not only in the 7 patients with extracranial involvement, but also in 7/12 patients with cranial GCA (58.3%). Along a median follow-up of 15 months [4.5-26.5], 4 relapses were reported. Notably, all the relapsers were males and showed both aortic and cranial involvement. In a multivariate model, male gender was the only predictor of relapse (p=0.02), while age at onset, clinical subset (cranial vs. extracranial) and steroid dose did not fit the model Conclusion: The use of PET in GCA is relevant in the assessment of extension of disease since a significative number of patients without cranial symptoms in the end resulted to have large vessel involvement. In addition, PET is useful in identifying patients with cranial involvement that have also aortic inflammation since they seems to have worse prognosis. Disclosure of Interests: None declared